Cuidado centrado na pessoa: reflexões da integração ensino-serviço na atenção básica. - LOPES, Willian da Silva (2021)
The person-centered clinical approach uses communication skills to establish the necessary link for the development of integral care. The National Curriculum Guidelines for the Medical Course point out that the student must concretize Person-Centered Care in health care. Thus, communication should be used as an aspect to be achieved in health care, consistent with the context found. Primary Care has become the focus of medical education because of principles of integrality, universality and equity, where one realizes the real context in which the health disease process is determined, and thus, it must be the stage for application of person-centered communication skills. Teaching-service integration should be worried about if person-centered care is being aplied and how this process can be improved for all actors involved in it. It is an evaluative research, with a qualitative and quantitative approach, using a perception person centered care questionnaire, in an observational, exploratory and transversal approach. The research universe was composed of three groups: doctors with and without teaching-assistance activity and medical internship. The research instrument was developed from aspects of doctor patient communication skills, identifying a perception person-centered. Uses Likert scale with 4 answers for each question asked, with the lowest scores related to person-centered medicine. The questionnaire also addressed three components of the person-centered method: exploring the experience of the disease (items 1 and 3), understanding the whole person(item 9) and finding a common problem management plan (items 2, 4 to 8 ) The good performance of professionals not connected to the university brings the reflection that the Teaching- service integration must be the done in order to cover all professionals that work in primary care. The improvement in adapting to the new nacional curriculum guidelines should Always be encouraged, especially when it is necessary to relate theory to practice, which allows the development of the health skills, especially those related to the person-centered clinic.